Autologous chondrocyte implantation for cartilage repair: current perspectives - Zellner J; Krutsch W; Pfeifer CG; Koch M; Nerlich M; Angele P (Orthopedic Research and Reviews, 2015)
Johannes Zellner,1 Werner Krutsch,1 Christian G Pfeifer,1 Matthias Koch,1 Michael Nerlich,1 Peter Angele1,2 1Department of Trauma Surgery, University Medical Center Regensburg, Regensburg, Germany; 2Sporthopaedicum, Regensburg, Germany Abstract: Over the last decade, regenerative treatment options have become the more routinely used techniques for treatment of cartilage defects, with predictable outcomes for their specific indications. For large chondral lesions in young patients, in particular, autologous chondrocyte implantation is the treatment of choice for restoration of joint health. This review focuses on indications, results, and outcome predictors of autologous chondrocyte implantation in comparison to other regenerative treatment procedures and discusses improvement options and future perspectives for autologous chondrocyte transplantation. As research activities are increasing in the field of regenerative joint therapy, recent developments may help to overcome remaining limitations step by step. Keywords: ACI, cartilage repair, matrix- associated autologous chondrocyte transplantation, microfracture, osteochondral transplantation